ChemInform Abstract: Metal‐Free Synthesis of Aryl Ethers in Water. Issue 19 (13th May 2014) - Lindstedt, Erik; Ghosh, Raju; Olofsson, Berit
Abstract Diaryliodonium triflates allow the arylation of various alcohols to give the corresponding aryl ethers.